Decoding the â€˜newâ€™ culture of roadside memorialisation in South Africa - Hagemann, Michael Eric (WritingThreeSixty, 2018)
Roadside memorials are such a common sight on this countryâ€™s roads that they barely warrant a second glance from passers-by, yet there was a time in recent memory when this was not the case. The increasing occurrence of these humble shrines indicates the entrenchment and expansion of a relatively â€œnewâ€ cultural practice that invites critical attention. In this paper, I intend to demonstrate that the emergence of this phenomenon in South Africa is a local adaptation of similar memorial traditions found elsewhere. By unpacking the forms and functions of these memorials as markers of private grief in public spaces, I will suggest that they reflect a secularising trend that in itself mirrors the demographics of our post-apartheid society.